The effect of nonleading foot placement on power and velocity in the fencing lunge - Gresham-Fiegel, G. N.; House, P. D.; Zupan, M. F. (The Journal of Strength and Conditioning Research, 2013)
The fencing lunge is a sport-specific movement, which helps the fencer score quickly and accurately. The fencing lunge is executed from a stable guard position, with the toes of the leading foot pointing directly toward the opponent. As a result of coach or fencer preference, however, the angle of the nonleading foot may vary greatly among fencers, from acute (nonleading foot facing forward) to obtuse (nonleading foot facing slightly backward). Studies in other sports suggest that foot placement may affect the efficient use of leg muscles and influence the power produced. Twenty-five experienced fencers from the U.S. Air Force Academy fencing team executed lunges from 3 specific angles of nonleading foot placement and from the natural stance. Foot placements were measured as the angle of the nonleading foot from the line of the leading foot and were delimited to an acute angle (45°), a perpendicular angle (90°), and an obtuse angle (135°). The angle of natural stance was also determined for each participant. Velocity and power were measured with a TENDO Weightlifting Analyzer, and the data were analyzed with repeated measures analysis of variance. Two statistical groups were considered, one containing all participants (N = 25) and a second group of participants with a natural forward-deviated stance (n = 15). Significant differences appeared between the nonleading foot placements in peak power (p < 0.001), average power (p < 0.001), peak velocity (p < 0.001), and average velocity (p < 0.001) in both groups. Pairwise t-test results indicated that, for both statistical groups, a perpendicular placement of the feet produced the greatest power and velocity during lunging.